High performance continuous-wave laser cavity enhanced polarimetry using RF-induced linewidth broadening - Tran, D-B-A; Peverall, R; Rosson, S; Manfred, KM; Ritchie, GAD (Optica Publishing Group, 2021)
We present precise optical rotation measurements of gaseous chiral samples using near-IR continuous-wave cavity-enhanced polarimetry. Optical rotation is determined by comparing cavity ring-down signals for two counter-propagating beams of orthogonal polarisation which are subject to polarisation rotation by the presence of both an optically active sample and a magneto-optic crystal. A broadband RF noise source applied to the laser drive current is used to tune the laser linewidth and optimise the polarimeter, and this noise-induced laser linewidth is quantified using self-heterodyne beat-note detection. We demonstrate the optical rotation measurement of gas phase samples of enantiomers of α-pinene and limonene with an optimum detection precision of 10 µdeg per cavity pass and an uncertainty in the specific rotation of ∼0.1 deg dm−1 (g/ml)−1 and determine the specific rotation parameters at 730 nm, for (+)- and (−)-α-pinene to be 32.10 ± 0.13 and −32.21 ± 0.11 deg dm−1 (g/ml)−1, respectively. Measurements of both a pure R-(+)-limonene sample and a non-racemic mixture of limonene of unknown enantiomeric excess are also presented, illustrating the utility of the technique.